PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH - Hilda Handayani; Fredi Ganda Putra; Yetri Yetri (Jurnal Tatsqif, 2018)
This study aims to develop the learning media through Macromedia Flash program software on building materials to test the feasibility of media developed through media experts, material experts, language experts and the response of learners to the learning media. This research type is research and development by using the procedure from the ADDIE method which stands for Analysis, Design, Development or Production, Implementation or Delivery, and Evaluations. The results obtained are Macromedia Flash-based learning media, as well as the results of the assessment of the media of learning based on the questionnaire. Media experts, material experts, and language linguists developed with two validation stages. The final validation of the Expert material reached an average score of 3.5 Experts 3.3 media and the linguist reached an average score of 4 it can be concluded that developed media valid and fit for use as a medium of learning. After that field experiment, based on the results of the questionnaire responses of learners on a small scale test scored 3.68 and on field trials scored 3.51, it can be concluded that the interest level of the media is on the category of very interesting. Based on all this, it can be concluded that the media is feasible and can be used as a medium of learning.